ABSURD THEATRE IN MARATHI: A STUDY OF C. T. KHANOLKAR’S EK SHUNYA BAJIRAO (CAHIERS MAGELLANES-NS, 2024)
C.T. Khanolkar's debut play, Ek Shunya Bajirao (Bajirao: A Cipher, 1966), is regarded as the first attempt to bring absurd theatre into Marathi. The current work seeks to investigate the characteristics of absurd theatre in Ek Shunya Bajirao. Like traditional Marathi plays, the play does not have a story. The climactic conclusion of the play is likewise surprising. Some of its distinguishing qualities include play within a play, spectators playing roles in the performance, fantasy, coincidence, symbolic usage of the stick, and so on.  Marathi theatre has a long history of theatrical activity. According to scholars, before independence, Marathi theatre was inspired by Karnataka's 'Yakshagana' and revolved around mythical themes. The adaptations of Shakespeare's and other European authors' plays, musical plays ("Sangeet Natak"), and social plays came next. The era from 1880 to 1930 was regarded as the golden age of Marathi theatre. However, following the golden time, Marathi Theatre experienced a dark phase from 1930 to 1955 due to the introduction of "Films". The post-independence era witnessed various advancements, including the establishment of Marathi Rajya Natya Spardha by the Maharashtra government to encourage Marathi theatre activities. Between 1955 and 1960, middle-class audiences returned to the theatre. Post 1960 to 90 is the most vibrant period which witnessed realistic and experimental Marathi theatre. Revival of folk drama, myths, existentialism, absurd dramatic techniques, and many more experiments were done on the stage. V.V. Shirwadkar, Vasant Kanetkar, Vijay Tendulkar, C. T. Khanolkar, and Mahesh Elkunchwar are a few dramatists who contributed to Marathi Theatre. This paper studies the features of absurd theatre in C.T. Khanolkar’s Ek Shunya Bajiraomold. It also attempts to study the playwright’s attempt to break down the traditional mould of plot and style.